Adult eczema in Italy: prevalence and associations with environmental factors. (2nd November 2014) - Pesce, G.; Marcon, A.; Carosso, A.; Antonicelli, L.; Cazzoletti, L.; Ferrari, M.; Fois, A.G.; Marchetti, P.; Olivieri, M.; Pirina, P.; Pocetta, G.; Tassinari, R.; et al.
Abstract Background Studies on the prevalence of eczema and atopic dermatitis (AD), and on the factors associated with these diseases, have been mostly performed in children, whereas studies on adult populations are lacking. Objectives To determine the prevalence of eczema and AD in the Italian adult population, and to investigate risk factors associated with the disease. Methods A postal screening questionnaire was administered to 18 357 randomly selected subjects aged 20–44 years in the Gene–Environment Interaction in Respiratory Diseases study, which involved seven centres distributed across northern, central and southern Italy. The questionnaire included items on the occurrence of doctor‐diagnosed eczema, asthma and hay fever, socio‐demographic characteristics and environmental exposures. Results In all, 10 464 (57.0%) subjects responded to the questionnaire. The prevalence of current eczema was 8.1% (95% CI: 7.6–8.7%), while the prevalence of eczema with asthma and/or hay fever (EAH), which was adopted as proxy of AD, was 3.4% (95% CI: 3.1–3.8%). About 60% of the subjects with current eczema reported the onset of the disease in adulthood. In multi‐variable models, the prevalence of eczema was significantly associated with female sex, older age, living close to industrial plants, high levels of heavy traffic near home and living in central‐southern Italy. Conclusions Eczema and EAH are highly prevalent in Italian young adults, especially in women. Our results suggest that adult onset is not unusual, and that environmental factors may influence the occurrence of eczema and EAH.